2011
DOI: 10.7166/21-1-66
|View full text |Cite
|
Sign up to set email alerts
|

Linking Projects to Business Strategy Through Project Portfolio Management

Abstract: In many organisations, a chasm exists between the development of strategy and its successful implementation. Failure to cross this chasm may ultimately result in strategy failure and the loss of competitive advantage, profits, and employment. Project Portfolio Management (PPM) is theorised as a management methodology that links a portfolio of projects to the business strategy. However, current literature lacks empirical evidence of the levels of employment, functionality, and success of the Project Portfolio M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 5 publications
1
17
0
2
Order By: Relevance
“…In 1998 Grundy [3] stated that the implementation phase is frequently the graveyard of strategy, and remains a neglected area in research. More recent literature has agreed with this statement [4]; [5]. It has been suggested that the solution could lie in making use of project portfolio management (PPM) e.g.…”
Section: Introduction and Problem Statementmentioning
confidence: 80%
See 1 more Smart Citation
“…In 1998 Grundy [3] stated that the implementation phase is frequently the graveyard of strategy, and remains a neglected area in research. More recent literature has agreed with this statement [4]; [5]. It has been suggested that the solution could lie in making use of project portfolio management (PPM) e.g.…”
Section: Introduction and Problem Statementmentioning
confidence: 80%
“…Although PPM has been well-researched ( [8]; [9]; [10]; [11]; [12]; [13]; [14]), there is still a lack of empirical evidence in the literature on achieving success through implementing PPM factors of best practice, especially in the South African environment ( [5]; [7]; [4]). This article aims to lay the groundwork for a study that will address the lack of empirical evidence on PPM in the South African context by deductively constructing a framework from the literature.…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
“…Foi possível agregar fatores (categorias e variáveis) através das correlações oriundas da literatura que ratificam e contribuem para a compreensão do objetivo geral deste estudo bem como servem para futuras pesquisas. Teoria internacional consistente foi pesquisada, para fundamentar a relação e estão citadas a seguir, de acordo com a ordem das referências utilizadas (Archer & Ghasemzadeh, 1999;Belout & Gauvreau, 2004;Boje, 1995;Buys & Stander, 2010;Cope et al, 2011;Harrison & Pelletier, 2000;Longman & Mullins, 2004;Meskendhal, 2010;PMI, 2012;Pressly, 2012;Srivannaboon & Milosevic, 2006;Van der Merwe, 2002;Ying & Yong-Dong, 2007;Yiu, 2008). A relação gerenciamento de projetos e estratégia empresarial foi analisada, tendo o Walt Disney…”
Section: Conclusões E Recomendaçõesunclassified
“…Thus, strategic alignment is fundamental to transform strategies into actions. The connection between the strategy and the selection and implementation of initiatives occurs through the execution of projects, with project portfolio management (PPM) being responsible for this alignment (BUYS;STANDER, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…the level of uncertainty as a critical issue on project portfolio management. All these problems result in a poor performance of project portfolio, with the selection of projects of low impact, very long product launch time, and failure rate above the accepted level (GOLDRATT, 1998;ELONEN;ARTTO, 2003;KLEINSCHMIDT, 2000;BUYS;STANDER, 2010).…”
Section: Introductionmentioning
confidence: 99%